1999
DOI: 10.1007/s001340051086
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and characteristics of an acute phase response following cardiac arrest

Abstract: (i) A marked acute phase response occurs regularly after cardiac arrest, but within the complexity of this situation the severity of hypoxia is not a predominant determinant of this response. (ii) Despite in vitro evidence for similarities in the oxygen dependent regulation of APP and EPO production, the oxygen sensitivity of these proteins in vivo is different. (iii) Measurements of APP are not revealing regarding infectious complications in the early phase after CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…An increase in CRP levels occurred irrespective to the cause of arrest, the estimated time of anoxia, the clinical course or patient's outcome and it was not different in patients with and without infectious complications within the first 2 days since hospital admission [90]. Similar findings were shown in a pediatric study, as CRP levels were elevated in all patients, survivors and nonsurvivors, within the first 24 h following arrest [91].…”
Section: Clinical Data On Inflammatory Biomarkerssupporting
confidence: 81%
“…An increase in CRP levels occurred irrespective to the cause of arrest, the estimated time of anoxia, the clinical course or patient's outcome and it was not different in patients with and without infectious complications within the first 2 days since hospital admission [90]. Similar findings were shown in a pediatric study, as CRP levels were elevated in all patients, survivors and nonsurvivors, within the first 24 h following arrest [91].…”
Section: Clinical Data On Inflammatory Biomarkerssupporting
confidence: 81%
“…These results are consistent with clinical studies that have described CA as a sepsis-like syndrome. (31, 32) IL-6 a mediator of the hepatic acute phase response and a potent inhibitor of CYPs. (33) Other ischemia models have shown that increased plasma IL-6 after injury is associated with decreased CYP activity.…”
Section: Discussionmentioning
confidence: 99%
“…After ROSC, factors affecting survival are recurrence of CPA, persistent hypotension, shock or myocardial dysfunction [11], hyperthermia [30], hypoglycemia [31] or hyperglycemia [32], coma for more than 24 hours, and sepsis with multiorgan failure syndrome [33,34]. Use of therapeutic hypothermia is a relatively new post-arrest intervention.…”
Section: Post-arrest Variablesmentioning
confidence: 99%